Sarcoma de la íntima de la arteria pulmonar que se presentó como embolismo pulmonar - Plata , María Camila; Rey, Diana Lucía; Villaquirán, Claudio; Rosselli, Diego (Iatreia, 2017)
Pulmonary artery sarcomas are extremely rare; due to their insidious growth, diagnosis occurs late and prognosis is poor. We present the case of a 33-year-old woman with a history of dyspnea, chest pain and syncope. An obstructing mass on the right ventricle, main pulmonary artery and right branch were interpreted as a possible pulmonary embolism.